Strategi Manajemen Dalam Implementasi Rekam Medis Elektronik Di Upt Laboratorium Kesehatan Daerah Kabupaten Nunukan - Satriana Silawati; St Rukaiyah; Syamsuddin Bidol (STIM-LPI Makassar, 2026)
This study aims to analyze and describe the management strategies applied by the Regional Health Laboratory UPT of Nunukan Regency in the planning, implementation, and management of Electronic Medical Records (EMR). In addition, this study seeks to identify and analyze the main obstacles encountered in EMR implementation from a strategic management perspective, as well as to describe the strategies used by management to manage or overcome these obstacles, which are then formulated into strategic recommendations for optimizing EMR implementation. This research uses a qualitative approach with a descriptive case study design. This approach was chosen to obtain an in-depth understanding of management strategies and the obstacles faced in EMR implementation at the Regional Health Laboratory UPT of Nunukan Regency, while considering the unique geographical context and resource limitations in the region. The results show that the Regional Health Laboratory UPT of Nunukan Regency applies adaptive, participatory, and contextual management strategies to address various challenges. The main constraints include limited technological infrastructure (unstable networks, outdated equipment), human resources issues (variability in competencies, resistance to change, lack of training/support), as well as unique geographical and regional resource challenges. Proactive management strategies such as budget advocacy, intensive coordination with the Health Office, personalized approaches to staff, utilization of “technology champions,” and strategic partnerships have successfully mitigated these obstacles, enabling EMR implementation to proceed despite challenging conditions.